Water and Sanitation in Dhaka Slums : Access, Quality, and Informality in Service Provision - Haque, Sabrina; Yanez-Pagans, Monica; Arias-Granada, Yurani; Joseph, George (Taylor and Francis, 2021)
Slum populations are commonly characterized to have poorly developed water and sanitation systems and speculated to access services through informal channels. However, there are limited representative profiles of water and sanitation services in slums, making it difficult to prioritize interventions that will make services safer for residents. This cross-sectional study examines quality and provision of access to water and sanitation services in government slums across Dhaka, Bangladesh. Access is overall high but is subject to quality issues related to safety, reliability, and liability. Services are often operated by informal middlemen at various stages of provision.